Aspirin Is Associated with Decreased Allogeneic Transfusions and Resource Utilization following Hip Fracture Care - Anoushiravani, Afshin A.; Sayeed, Zain; Mori, Benjamin V.; Padela, Muhammad T.; Barinaga, Gonzalo; Cagle, Paul J.; Saleh, Khaled J. (The Journal of Hip Surgery, 2021)
The purpose of our study is to assess the relationship and compare the impact of aspirin, enoxaparin, and warfarin use on postoperative anemia, allogenic transfusions, and resource utilization following hip fracture fixation. This is a retrospective study at a Level 1 trauma center with 450 geriatric hip fracture patients who underwent hip fracture surgery and chemoprophylaxis. Hip fracture patients were separated into three cohorts depending on the type of chemoprophylaxis administered aspirin, enoxaparin, or warfarin. Initially, all three cohorts were assessed for baseline characteristics, postoperative anemia, transfusion rates, and resource utilization. Next, aspirin and enoxaparin were comparatively evaluated for the same variables. Four hundred and fifty patients met inclusion criteria for the first portion of this study. No baseline variance was evident among the three cohorts except for body mass index (p = 0.007) and diagnosis of congestive heart failure (p = 0.001). Outcomes were insignificant for in-hospital mortality (p = 0.19), postoperative anemia (p = 0.43), hemoglobin levels (p = 0.91), and ∆hemoglobin (p = 0.99), length-of-stay (p = 0.12), disposition (p = 0.13), and 30-day readmission (p =0.09). The transfusion rate (p < 0.001) and hospital cost (p = 0.01) varied significantly among the prophylactic cohorts. Three hundred and eighty nine patients met inclusion criteria for the aspirin and enoxaparin comparison. Baseline characteristics between the cohorts only revealed a significant variance for age (p = 0.03). Outcomes did not vary significantly among aspirin and enoxaparin cohorts; however, hospital cost was 12.3% greater in patients receiving enoxaparin (p = 0.01). Our study compares administration of aspirin, warfarin, and enoxaparin as means of chemoprophylaxis following hip fracture repair. Analyses of outcomes demonstrated patients receiving warfarin were more likely to require transfusions. Additionally, when compared with aspirin, resource utilization was 16.9 and 12.3% greater with warfarin and enoxaparin, respectively. Thus, our study suggests that aspirin is a safe and cost-effective option for chemoprophylaxis following hip fracture fixation.
Keywords: hip fracture care; cost-effectiveness; VTE chemoprophylaxis; aspirin